Interannual and seasonal variability of NOx observed at the Mt. Cimone GAW/WMO global station (2165 m a.s.l., Italy). (15th March 2021) - Cristofanelli, P.; Gutiérrez, I.; Adame, J.A.; Bonasoni, P.; Busetto, M.; Calzolari, F.; Putero, D.; Roccato, F.
Abstract: In this work, we present and analyze a dataset of near-surface NO and NO2 observations carried out at the Mt. Cimone WMO/GAW global station (CMN, Italy, 2165 m a.s.l.) from 2015 to 2019. The purpose of this work is to provide a first characterization of NO and NO2 variability over different time scales, as well as to obtain preliminary information about transport processes able to affect the observed variability. NO was characterized by a peak in February–March (mean value: 0.08 ppb), while in summer the typical levels were near or lower than the detection limit. NO2 values maximized in winter (0.32–0.37 ppb) and minimized in summer (0.21 ppb in June). The evident NO and NO2 diel cycles point towards a joint role of vertical transport of air masses from the regional planetary boundary layer (PBL) and photochemistry. We combined nighttime observations (less affected by direct transport from the regional PBL) and 3D back-trajectories, calculated by the FLEXTRA model (2015 -2018), to analyze how long-range atmospheric circulation could impact NO2 observations. Even if some caveats should be considered when commenting results from back-trajectory analysis (i.e. NOx removal by oxidation processes not represented, possible residual impact of regional PBL air masses, impact of adding/removing a single year from the analysis), some robust outcomes can be considered: the atmospheric transport from northern Africa and the Mediterranean basin was tagged to baseline NO2 values, while the highest values were related to atmospheric circulation overpassing central/western Europe (spring) and North Italy (spring and summer). Less robust relationship were found between high NO2 values and air masses passing over central/western Europe (winter) and eastern Europe (winter and summer). On the other side, mountain thermal wind regime represents an important process for the occurrence of high NO2 events by transporting polluted air masses from the regional PBL to CMN. Our analysis suggested that it is not possible to define a unique set of O3 /NOx threshold values able to discriminate the photochemical ages of air masses as done in previous studies; these values must be tuned as a function of the season and, possibly, of the measurement site. Finally, we segregated CMN observations as a function of conditions representative for the presence of free tropospheric- or PBL-affected air masses: higher NOx were observed under conditions representative for the transport of air masses from the regional PBL; the differences between the two regimes are maximized in winter for NO and in summer-autumn for NO2 .